Postinflammatory hypopigmentation - V. Vachiramon (2018)
Postinflammatory hypopigmentation is a common cause of acquired hypopigmentary disorders. It can be a result of cutaneous inflammation, injury or dermatological treatment. There are also many specific conditions that present with hypopigmentation other than postinflammatory hypopigmentation. Most cases of postinflammatory hypopigmentation improve spontaneously within weeks or months if the primary cause is ceased; however, it can be permanent if there is complete destruction of melanocytes. This article reviews the aetiology, pathogenesis, clinical features, differential diagnosis and therapeutic options for postinflammatory hypopigmentation. Click for the corresponding questions to this CME article. © 2011 British Association of Dermatologists.